2005
DOI: 10.1002/pola.20784
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and phase behavior of side‐chain cholesteric liquid‐crystalline elastomers

Abstract: A series of new side‐chain cholesteric elastomers derived from cholesteryl 4‐(10‐undecylen‐1‐yloxy)‐4′‐ethoxybenzoate and phenyl 4,4′‐bis(10‐undecylen‐1‐yloxybenzoyloxy‐p‐ethoxybenzoate) was synthesized. The chemical structures of the monomers were confirmed by elemental analyses, Fourier transform infrared, and 1H NMR and 13C NMR spectra. The mesomorphic properties of elastomers were investigated with differential scanning calorimetry, thermogravimetric analysis, polarizing optical microscopy, and X‐ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For nematic structure, no peak appeared in SAXS curve, but a broad peak at 2θ ≈ 20° in WAXD curve was observed. For cholesteric structure, no peak appeared in SAXS curve, however, we discovered that a broad peak occurred at 2θ = 16–18° in WAXD curve 33–35. Representative XRD curves of P 3 and P 6 are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For nematic structure, no peak appeared in SAXS curve, but a broad peak at 2θ ≈ 20° in WAXD curve was observed. For cholesteric structure, no peak appeared in SAXS curve, however, we discovered that a broad peak occurred at 2θ = 16–18° in WAXD curve 33–35. Representative XRD curves of P 3 and P 6 are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 91%
“…In previous study, we reported the synthesis and properties of side‐chain cholesteric LCEs derived from smectic, nematic, and nonmesogenic crosslinking agent, respectively 33–35. In this study, new cholesteric LCEs based on chiral mesogenic crosslinking agent were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic route of the intermediate compounds is shown in Scheme . Menthyloxyacetic acid ( 1 ), 4‐menthyloxyacetoxybenzoic acid ( 3 ), 4‐(2‐hydroxy‐ethoxy)benzoic acid ( 5 ), 4‐(6‐hydroxyhexyloxy)benzoic acid ( 6 ), and 4‐(2‐undec‐10‐enoyloxyethoxy)benzoic acid ( 7 ) were prepared according to the method reported by Hu et al43–45…”
Section: Methodsmentioning
confidence: 99%
“…The synthetic route of the intermediate compounds is shown in Scheme 1. Menthyloxyacetic acid (1), 4-menthyloxyacetoxybenzoic acid (3), 4-(2-hydroxy-ethoxy)benzoic acid (5), 4-(6-hydroxyhexyloxy)benzoic acid (6), and 4-(2-undec-10enoyloxyethoxy)benzoic acid (7) were prepared according to the method reported by Hu et al [43][44][45] 4-(6-Undec-10-enoyloxyhexyloxy)benzoic Acid (8) The synthesis of 8 is similar to that for 7 as described above. 4-Hydroxybiphenyl-4 0 -(2-undec-10-enoyloxyethoxy) benzoate (9) 4-(2-Undec-10-enoyloxyethoxy)benzoyl chloride was prepared through the reaction of 7 with excess thionyl chloride.…”
Section: Synthesis Of the Intermediate Compoundsmentioning
confidence: 99%
“…However, a broad peak at 2y % 20 and 2y % 17 was observed in the WAXD curves of nematic and cholesteric polymers, respectively. 28,29 Therefore, it is a very important characteristic for judging cholesteric structure that broad diffraction angles appear at lesser angles than those of nematic structures in WAXD. It suggests that the average distance between two neighbor LC molecules within the layers of the mesophase become broad due to the helix structure of cholesteric LC polymers.…”
Section: Xrd Analysismentioning
confidence: 99%